The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5649/jjphcs.42.56
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Number of Drugs among Elderly Patients Hospitalized in a Rehabilitation Ward

Abstract: Patients admitted in rehabilitation wards are usually older than those in general wards. Since elderly patients suffer from multiple co-morbidities thus showing a variety of symptoms, they are often at risk of polypharmacy. In the present retrospective observational study, we aimed to search for clinical characteristics of patients who were associated with factors influencing the number of drugs at discharge. One hundred and twenty-four patients (aged ≥65 years) who were admitted to rehabilitation wards in Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In order to avoid drug interactions and severe adverse drug effects, "high-risk drugs" that require safety management (e.g., anticoagulants, antidiabetic drugs, and anti-epileptic agents) require the implementation of pharmaceutical management services such as continuous drug administration guidance and adverse drug effect management [11]. Ogawa et al reported that approximately 70% of patients in convalescence rehab wards received high-risk drugs and that pharmacist involvement was therefore an important aspect of appropriate drug administration to ensure safety during rehabilitation [2]. Fujiwara et al found that convalescence rehab wards implemented drug administration guidance, test value checks, adverse drug effect monitoring, and other ward services at significantly lower rates than general hospital wards [12], and reported that both physicians and nurses were strongly in favor of providing drug administration guidance and adverse drug effect monitoring when self-management was in practice and when prescriptions were changed [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid drug interactions and severe adverse drug effects, "high-risk drugs" that require safety management (e.g., anticoagulants, antidiabetic drugs, and anti-epileptic agents) require the implementation of pharmaceutical management services such as continuous drug administration guidance and adverse drug effect management [11]. Ogawa et al reported that approximately 70% of patients in convalescence rehab wards received high-risk drugs and that pharmacist involvement was therefore an important aspect of appropriate drug administration to ensure safety during rehabilitation [2]. Fujiwara et al found that convalescence rehab wards implemented drug administration guidance, test value checks, adverse drug effect monitoring, and other ward services at significantly lower rates than general hospital wards [12], and reported that both physicians and nurses were strongly in favor of providing drug administration guidance and adverse drug effect monitoring when self-management was in practice and when prescriptions were changed [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore a high risk of adverse drug reactions among the elderly [1]. In addition, a study of elderly patients in convalescence rehab wards showed that 70% of patients used at least one "high-risk drug," such as anticoagulants and cardiovascular agents [2]. Between 37% and 78% of patients who have had a stroke suffer from dysphagia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often the case that stroke patients with CKD are necessarily associated with polypharmacy. Adverse drug reactions or the risk of adverse drug interactions caused by polypharmacy has been reported globally and has become a major obstacle in the safe and reliable treatment of a stroke [20]. In particular in the convalescent rehabilitation ward, we cannot deny the possibility that the expression of adverse drug reactions affects FIM.…”
Section: Discussionmentioning
confidence: 99%
“…About 85% of inpatients are elderly, aged ≥ 65 years [1], most of whom have underlying diseases such as hypertension and diabetes mellitus. Furthermore, they are at higher risk of polypharmacy (the number of drugs used exceeds 5 to 6) because of the use of anticoagulants, analgesics, and anti-ulcer drugs in the acute stage ward, and sleep disorders during hospitalization [2,3]. Convalescent rehabilitation wards are more appropriate than acute stage wards for pharmacists to examine the types, use, and dosage of medical drugs for patients with long-term hospitalization.…”
Section: Introductionmentioning
confidence: 99%